Time for a new language for asthma control: results from REALISE Asia - Price D; David-Wang A; Cho SH; Ho JCM; Jeong JW; Liam CK; Lin JT; Muttalif AR; Perng DW; Tan TL; Yunus F; Neira G (Journal of Asthma and Allergy, 2015)
David Price,1,2 Aileen David-Wang,3 Sang-Heon Cho,4 James Chung-Man Ho,5 Jae-Won Jeong,6 Chong-Kin Liam,7 Jiangtao Lin,8 Abdul Razak Muttalif,9 Diahn-Warng Perng,10,11 Tze-Lee Tan,12 Faisal Yunus,13 Glenn Neira14 On behalf of the REcognise Asthma and LInk to Symptoms and Experience (REALISE) Asia Working Group 1Centre of Academic Primary Care, University of Aberdeen, Aberdeen, UK; 2Research in Real Life, Singapore; 3University of the Philippines-Philippine General Hospital, Manila, Philippines; 4College of Medicine, Seoul National University, Seoul, Republic of Korea; 5Department of Medicine, University of Hong Kong, Hong Kong, Special Administrative Region of the People's Republic of China; 6College of Medicine, Inje University, Goyang, Republic of Korea; 7Department of Medicine, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia; 8China-Japan Friendship Hospital, Beijing, People's Republic of China; 9Institute of Respiratory Medicine, Kuala Lumpur, Malaysia; 10School of Medicine, National Yang-Ming University, 11Department of Chest Medicine, Taipei Veterans General Hospital, Taipei, Taiwan; 12National University Hospital, Singapore; 13Persahabatan Hospital, University of Indonesia, Jakarta, Indonesia; 14Medical Affairs Department, Mundipharma Pte Ltd, Singapore Purpose: Asthma is a global health problem, and asthma prevalence in Asia is increasing. The REcognise Asthma and LInk to Symptoms and Experience Asia study assessed patients' perception of asthma control and attitudes toward treatment in an accessible, real-life adult Asian population. Patients and methods: An online survey of 2,467 patients with asthma from eight Asian countries/regions, aged 18–50 years, showed greater than or equal to two prescriptions in previous 2 years and access to social media. Patients were asked about their asthma symptoms, exacerbations and treatment type, views and perceptions of asthma control, attitudes toward asthma management, and sources of asthma information. Results: Patients had a mean age of 34.2 (±7.4) years and were diagnosed with asthma for 12.5 (±9.7) years. Half had the Global Initiative for Asthma-defined uncontrolled asthma. During the previous year, 38% of patients visited the emergency department, 33% were hospitalized, and 73% had greater than or equal to one course of oral corticosteroids. About 90% of patients felt that their asthma was under control, 82% considered their condition as not serious, and 59% were concerned about their condition. In all, 66% of patients viewed asthma control as managing attacks and 24% saw it as an absence of or minimal symptoms. About 14% of patients who correctly identified their controller inhalers had controlled asthma compared to 6% who could not. Conclusion: Patients consistently overestimated their level of asthma control contrary to what their symptoms suggest. They perceived control as management of exacerbations, reflective of a crisis-oriented mind-set. Interventions can leverage on patients' trust in health care providers and desire for self-management via a new language to generate a paradigm shift toward symptom control and preventive care. Keywords: asthma control, attitudes, perception